Design of mathematics learning in the grand mosque of palembang. (March 2020) - Martadinata, I; Somakim; Darmawijoyo; Araiku, J
Abstract: This study aims to describe the role of the context of the Grand Mosque of Palembang to support the mathematics learning process and produce learning trajectories to help students in understanding quadrilateral material (square, rectangle, and isosceles trapezoid) with RME approach. The methodology in this research is design research, consisting of preliminary design, design experiment, and retrospective analysis. The subjects are seventh graders of MTSN 1 Palembang. The instruments in this research are videos, documentation, student activity sheets, pre-test, and post-test. The results show that the context of the Grand Mosque of Palembang helps students to compare and connect the perimeter and area of a rectangular plane. All strategies and models that students find, describe and discuss, show how the construction and contribution of students help their initial understanding of the topic. In experience based activity, comparing and connecting the perimeter and area of rectangular plane holds an important role in transitioning from informal to formal levels.